Implementation of Instagram Media in Arabic Language Learning - Malik, Lalu Maulana; Nabiilah, Alaikin; Syafril R, Raihan Ammar; Mustofa, Syaiful (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2024)
يعد انستغرام أحد من الوسيلة الاجتماعية التي يطلبها جيل الشباب كثيرًا في إندونيسيا. استنادًا إلى بيانات نابليون كات، هناك 113.24 مليون مستخدم انستغرام في إندونيسيا، بنسبة 67.6%  المستخدمين الذين تتراوح أعمارهم بين 18 و34 عامًا. يتمتع انستغرام بإمكانيات كبيرة يمكن استخدامها كمنصة تعليم اللغة العربية الإبداعية والمبتكرة والحديثة والمثيرة للاهتمام. الهدف من هذا البحث هو معرفة كيف أن استخدام وسيلة الاجتماعية إنستغرام لسهولة فهم اللغة العربية من خلال محتوى متنوعة، ويدعم تعلم اللغة العربية الإبداعي والإبتكار، ويقدم تعليم اللغة العربية الممتعة من خلال وسيلة إجتماعية إنستغرام. يستخدم هذا البحث المدخل الكيف مع تقنيات جمع البيانات، وهي الملاحظة والوثائق. بشكل تقليل البيانات وعرض البيانات و النتيجة. إستخدام البحث أن وسيلة استغرام .@kursus_arab_alazhar إستخدام على أربعة أنواع من المحتوى التعليمي، وهي مقاطع الفيديو المحدثة، ومقاطع الفيديو التعليمية، ومقاطع الفيديو رسوم المتحركة، و قواعد النحو والصرف. تظهر نتائج هذا البحث يمكن استخدام انستقرام والاستفادة كوسيلة لسهولة فهم اللغة العربية من خلال محتوى متنوعة، وبدعم تعليم اللغة العربية الإبداعي والمبتكر، ويقدم تعليم اللغة العربية الممتعة من خلال وسيلة الاجتماعية إنستغرام.   Instagram is one of the most favored social media platforms among the youth in Indonesia. According to data from Napoleon Cat (a social media management tool), there are 113.24 million Instagram users in Indonesia, with a percentage of 67.6% of the total being users aged 18-34 years. Instagram holds significant potential as a creative, innovative, modern, and engaging platform for Arabic language learning. The purpose of this research is to investigate the utilization of the Instagram social media platform in facilitating the understanding of the Arabic language through diverse content, supporting creative and innovative Arabic language learning, and introducing enjoyable Arabic language learning through Instagram. This research employs a descriptive qualitative method with data collection techniques such as observation and document analysis. Data analysis in this study includes data reduction, data display, and drawing conclusions. The research focuses on the Instagram account @kursus_Arab_alazhar, which incorporates four types of learning content: muhadatsah videos, tutorial videos, animated videos, as well as nahwu and shorof principles. The results of this study indicate that Instagram as a social media platform can be effectively used and leveraged to facilitate the understanding of the Arabic language through diverse content, support creative and innovative Arabic language learning, and introduce enjoyable Arabic language learning through Instagram.